Adsorption/desorption performance of volatile organic compounds on electrospun nanofibers. Issue 124 (30th November 2015) - Chu, Lanling; Deng, Siwei; Zhao, Renshan; Zhang, Zhao; Li, Chen; Kang, Xuejun
Abstract : Electrospun nanofibers possess the advantages of the certain selectivity, favorable adsorption/desorption efficiency, short adsorption equilibration time and preferable regeneration and can be a potential adsorbent for VOCs. Abstract : The objective of this study was to investigate the adsorption/desorption performance of volatile organic compounds (VOCs) on electrospun nanofibers. A homemade rational adsorption experimental setup was used to conduct performance tests on the nanofibers measuring the selectivity, adsorption/desorption efficiency, adsorption equilibration time, regeneration and temperature effects. The VOCs adsorbed on different adsorbents, followed by desorption (thermal and/or solvent), were analyzed using capillary gas chromatography. Three nanofibers, including polystyrene (PS) nanofibers, acrylic resin (AR) nanofibers, and polystyrene–acrylic resin (PS–AR) composite nanofibers, three comparison materials, including activated carbons (ACs), carbon nanotubes (CNTs), and carbon fibers (ACFs), as well as ten VOCs, including n -butanol, toluene, chlorobenzene, anisole, nitrobenzene, dichloromethane, ethyl acetate, benzene, acetone and n -hexane, were partly utilized in different performance experiments. The results revealed that the nanofibers exhibited a certain selectivity and the best thermal desorption efficiency compared to all comparison materials. What is more, electrospun nanofibers spent short time reaching adsorption equilibration, favorable regeneration and temperature effect. It showed that electrospun nanofibers can be a potential adsorbent for VOCs.